Political connection, board diversity, director’s busyness and company performance: Empirical evidence from Indonesia - Riska, Sonia Ayesha; Handayani, Wuri (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This research examines the influence of political connections, board diversity, and director busyness on firm performance, while considering the moderating role of ownership structure. The sample comprises 440 firm-year observations of companies listed on the Indonesia Stock Exchange during 2014–2024. Indonesia provides a relevant setting due to the widespread presence of politically exposed individuals and limited transparency in regulations related to political affiliations. This study offers two main contributions. First, it emphasizes the positive role of political connections in improving firm performance and provides implications for regulatory policies. Second, it provides insights into board composition, particularly female representation, which remains relatively low in Indonesia. The results indicate that political connections significantly enhance firm performance, suggesting that government ties create strategic benefits. Similarly, Board diversity shows a positive effect, highlighting the contribution of women in improving decision-making quality and risk management. In contrast, director busyness is not significantly related to company performance. Further moderation analysis shows that managerial ownership weakens the positive effect of political connections on performance, but does not significantly impact the relationship between board diversity or director engagement and firm performance.